'And they shall Beat their Swords into…Scrapers': Two Case Studies in the Vocabulary of Jewish Palestinian Aramaic. (18th August 2018) - Mastey, Emmanuel
Abstract: The paper discusses two agricultural implements mentioned briefly in Talmud Yerushalmi (also known as 'Palestinian Talmud'; edited c. 375 ce ), in vernacular Jewish Palestinian Aramaic, namely ( ? bwyyn ) and ( mgzyyn ). The former is a scraper used to clean dirt off the ploughshare. The latter is a pruning-hook. Both terms are analysed with regard to their lexical and morphological aspects. Special attention is paid to their Syriac cognates. Arabic vernaculars of the Levant are also examined in relation to these appliances, as they may contain remnants from Aramaic and Hebrew substrata. Although the linguistic level remains the main focus of the study, an attempt is made to identify both implements with actual tools known from archeological excavations, as well as from traditional farming methods still employed today; this is done in order to establish a firm link between the lexemes under discussion and material reality.